The Notion of ẓarf in the Arabic Linguistic Tradition - Olivieri, Simona (Folia Orientalia, 2026)
This contribution aims at presenting the arguments produced by Arabic grammarians in the discussion on the ẓarf. By providing different viewpoints, the paper addresses various aspects of the issue, focusing in particular on its definition(s) and features, as well as its collocation within the overall Arabic grammatical system.